Follow-up and Survivorship in Head and Neck Cancer. Issue 7 (July 2016) - Simcock, R.; Simo, R.
Abstract: Treatments for head and neck cancer are improving, yet they remain toxic and challenging. The incidence of some forms of head and neck cancer (e.g. oropharyngeal) is rising. This creates an enlarging cohort of survivors with complex needs. These needs may be overlooked and undertreated. This overview presents evidence for the unmet survivorship needs of head and neck cancer patients and identifies strategies for the recognition and remedy of these needs in the clinic. There is sufficient evidence to challenge services to redesign follow-up strategies around unmet need using the full multidisciplinary team and to widen focus away from a sole aim of recognition and treatment of recurrent disease. Problems presented include depression, comorbid disease, second malignancy, alcohol and nicotine dependence, eating and drinking difficulties (including dysphagia, dental problems, trismus and sense disturbance) and hypothyroidism.